STRATIFIKASI SIMPANAN KARBON DIATAS PERMUKAAN TANAH PADA LAHAN GAMBUT PASANG SURUT DAN LEBAK - Siti Nur Zakiah; Nur Wakhid; Dedi Nursyamsi (Research Center for Biology-Indonesian Institute of Sciences, 2017)
The carbon stored in peatlands is huge not only from soil but also from vegetation. Carbon stocks can decrease when there are human activities such as land use changes. Measuring and monitoring carbon stocks are necessary as the basis for assessment of the impact of land management technology applications to conservation and carbon emissions associated with sustainable management system of peatland. The purpose of this study was to determine the stratification of above ground C-stock in tidal peatland and fresh water swampland. Above ground C-stock stratification based on the types of vegetation. The stratification was conducted to distinguish vegetation conditions based on the volume of biomass and carbon content in an observation plot. The measurement of above ground C-stock was carried out by destructive and non destructive refers to Hairiah K and Rahayu (2007), after that the estimation of carbon stockswas conducted on tidal peatland (land use rubber + pineapple, rubber folk and shrubs) and peat in fresh water swampland (land use rubber 4-5 years and 2-3 years). The results showed that the types of vegetation, plant density and management affect of carbon stocks. Carbon stocks in tree vegetation are higher than shrubs. The high of plant density affects the sunlight used for photosynthesis, through photosynthesis, CO2 is absorbed and converted by plants into organic carbon in the form of biomass. Arrangement and maintenance of the plant affects the storage of carbon in a land use.